Influence of brand awareness, brand image, and digital marketing on purchase interest in pt duta global Indonesia - Femendy, Femendy; Nora Pitri Nainggolan (SEAN Institute, 2024)
Every company should strive to provide customers with products that meet countless consumer desires and are easily changed. Because not all products marketed meet consumer needs, consumers must make the right decisions in the purchasing process so that their needs are satisfied with the benefits of the products they buy. This research aims to determine the influence of brand awareness, brand image and digital marketing on purchasing interest at PT Duta Global Indonesia. This research design uses a research design and quantitative research methods. Data collection techniques by distributing questionnaires to 100 respondents. The results of this research show that Brand awareness, Brand image, and Digital marketing simultaneously have a positive and significant effect on purchasing interest at PT Duta Global Indonesia. The results of the coefficient of determination test show that the influence of Brand awareness, Brand image, and Digital marketing on purchasing interest at PT Duta Global Indonesia is 62.5 percent, while the rest is influenced by other variables not examined in this research.